From ductile to brittle deformation – the structural development and strain variations along a crustal-scale shear zone in SW Finland - Torvela, T.; Ehlers, C. (TRABAJOS DE GEOLOGÍA, 2010)
This study demonstrates the impact of variations in overall crustal rheology on crustalstrength in relatively high P-T conditions at mid- to lower mid-crustal levels. In a crustal-scale shearzone, along-strike variations in the rheological competence result in large-scale deformation partitioningand differences in the deformation style and strain distribution.